Suporte ambiental: uma estratégia para educação infantil inclusiva - Bredariol, Ana Cláudia Pinto (2006)
The physical space of an Institution of necessary Infantile Education to become an environment, that is, to provide situations that facilitate the interpersonal relations and above with everything allowed the emergency of diverse forms of expression, the unexpected one, knowing them spontaneous infantile. In this study the pertaining to school space called surrounding educational physicist being considered as important curricular element, taking in account aspects as: elements that condition the organization of the spaces, criteria for one adjusted organization of the spaces, paper of the educator in the organization of the space and paper of the educator in the acceptance of the diversity. This study it emphasized educational - physical environment as an important ally of the inclusive school, where pedagogical proposals must challenging and be diversified, offering chances of quality for all, also to the children with educational necessities special. It was considered evaluation of educational the physical environment as essential for the elaboration and curricular planning, as well as a facilitator in the educative process. This study it had as objective generality: To investigate the importance of educational - physical environment in the construction of a proposal inclusive under the optics of the infantile educator, and was characterized as being descriptive - exploratory, using as base the qualitative and quantitative analysis of the data. To reach the considered objective, three distinct stages had been carried through: initial qualification (establishment of the base line); application of half-structuralized interview (inquiry of the perception of the educator in relation to educational the physical environment) and application of a Script pair analysis of educational the physical environment of each participant educator (evaluation of the quality of the educational environment). 29 educators of public and private institutions had participated infantile of the city of Uberaba. The joined data had shown that despite the majority of the professors presenting superior formation, many, they do not present desirable formation for the development of programs and actions directed to the inclusive infantile education. It can also be concluded that the educators value the environment as an important ally in the learning process, but do not identify its functions, the importance of different resources, the abilities developed from the different space arrangements, the chances that must be offered. Of one the educators had been general do not obtain to characterize its educational physical environment although to recognize its importance in the planning and struturation of its proposal pedagogical. They relate different acquisitions in the development of the child to the ambient situations, however they do not present a proposal definite of chances that the access of all facilitates and any child of its room. The educators had identified the diversities of its populations presents in the educational environment, however they point insatisfações in the conduction of its action in result of great groups of children for room, diversity of pupils, professional unpreparedness, lack of support and precarious conditions of work. One concludes that to think about inclusive education or proposal that makes possible it, it is a challenge for researchers and educators who act in the area of Special Education. This challenge still becomes bigger when we deal with forms to think or to act of professionals who are living deeply in the practical a diversity of the inclusion, or when we consider changes so that they are taken care of and respected the peculiarities presented for the diversity. For improvement of the practical ones of intervention in the education, one becomes necessary that the educator knows to diagnosis the situation where is inserted and to consider alternative of action, to modernize how much to the new trends and strategies of education, to establish a vision criticizes regarding its action.